Thursday

July 31, 2014

July 31, 2014

Posted by **Dee** on Monday, November 18, 2013 at 7:41pm.

4^(x − 3) = 3^(2x)

x = _____

- college algebra -
**Henry**, Tuesday, November 19, 2013 at 9:09pm4^(x-3) = 3^(2x)

(x-3)*Log4 = 2x*Log 3

Divide both sides by Log 4:

x-3 = 2x * 0.79248 = 1.5850x

x - 1.5850x = 3

-0.5850x = 3

X = -5.1282

**Related Questions**

college algebra - Solve the exponential equation using logarithms. Give the ...

exponential equation-Algebra - Solve the exponential equation. Express the ...

Algebra 2 - How do you solve this exponential equation using logarithms? 2*5^x=...

Algebra-please check my answers - Solve the equation by expressing each side as ...

trigonometry - Use logarithms and the law of tangents to solve the triangle ABC...

College Algebra - Solve the exponential equation algebraically: 2^x+1=5^2x

calculus - solve the exponential equation. Express the solution in terms of ...

Logarithms - What's the fastest way to find Anti Logarithms(not using ...

Logarithms - What's the fastest way to find Anti Logarithms(not using ...

Logarithms - What's the fastest way to find Anti Logarithms(not using ...